WATER CRISIS AND WATER MANAGEMENT STRATEGIES IN THE SYRIAN REFUGEE SETTLEMENTS IN LEBANON - Nourelhuda Elmanaya; Harjito; Eri Sofiatry (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2022)
Water scarcity is an urgent issue in the Middle East, and rapid population growth caused by the refugee crisis impose further demand on the water supply in the country. This research was carried out in order to portray the water crisis in Lebanon analyzing the water governance policies that have been implemented by the Lebanese government, especially after the Syrian refugee crisis. The aim of this case study is to describe the main reasons behind the water scarcity in Lebanon nowadays, besides analyzing the water governance strategies implemented by the Lebanese government and other international organizations to address this crisis within the context of the Syrian refugee crisis in Lebanon. Findings indicate that several actions must be done to minimize water stress in Lebanon if a political settlement in Syria is established and refugees begin to return to Syria. However, even if Syrian refugees return home and Lebanon's population declines, water scarcity will remain an issue that must be addressed. These long-term plans include agricultural water-use reform and, eventually, government water-sector reform.